PRIMARY PANTOMIES: GAMES AND STORIES - Mannonov Sardor Shukhratjonovich; Fazlieva Zebo Kamarbekovna (Scholar Express Journal, 2021)
This article analyzes the early stages of the formation of theatrical art, its historical roots and hunting ceremonies, religious rites and various dances, games and pantomimes that occurred in those times
Keywords: Dance; pantomime; mime; play